FAR EASTERN REPUBLIC (1920-1922): CASE OF BOLSHEVIKS' MANEUVER - Ivanovich Baksheev, Andrei; Alexandrovich Novikov, Pavel; Pavlovna Musat, Raisa; Petrovna Shtump, Svetlana; Vladimirovich Rakhinsky, Dmitry (Revista Inclusiones, 2020)
The article focuses on the analysis of a historical byway of the Russian Far East – the conditions for emergence, the fight for independence and loss of autonomy of the Far Eastern Republic that existed in 1920-1922. The purpose of the study: the analysis of the conditions for emergence, the fight for independence and loss of autonomy of the Far Eastern Republic. Through the use of the principle of objective historicism, the synchronous method and the method of historical modeling, the authors analyze the features of the Civil War in the Far East, the foreign-policy basis of the creation of the Far Eastern Republic, the reasons for the emergence of the Far Eastern Republic, the fight of the Far Eastern Republic military with the Whites and the invaders, the relations of Soviet Russia and the Far Eastern Republic and the reasons for the Far Eastern Republic's loss of autonomy. The authors conclude that the Far Eastern Republic was a buffer state that, according to its creators, was bound to disappear from the political map of the world after protecting Soviet Russia from Japanese aggression.